Low-lead inorganic perovskite scintillator and preparation method and application thereof
By using cation exchange promoters and alkaline zinc bromide solution in the solid-liquid interface reaction system, the Cs4PbBr6/CsPbBr3 phase was formed and Zn2+ doping was achieved, and the radiation stability of Cs-Pb-Br perovskite scintillator was solved. and the deficiency in lead content, efficient X-ray imaging and radiation detection are achieved.
Patent Information
- Application Number
- CN202411522346.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
The existing Cs-Pb-Br perovskite scintillators have shortcomings in terms of radiation stability and lead content, which is difficult to meet the needs of efficient X-ray imaging.
By adding cation exchange promoter 3-aminopropyltriethoxysilane to the solid-liquid interface reaction system and adding a basic zinc bromide solution containing a large amount of Zn2+, the water-assisted cation exchange reaction is triggered to form Cs4PbBr6/CsPbBr3 substances The phase is achieved and the large doping of Zn2+ is achieved, replacing the toxic Pb2+, and a low-lead inorganic perovskite scintillator is obtained.
It has achieved a low-lead inorganic perovskite scintillator with excellent optical properties and low lead content, with high light yield, suitable for X-ray imaging and radiation detection, and has a short period of preparation method and mild conditions, making it easy to produce large-scale industrially.
Smart Images

Figure CN119391418A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of radiation detection technology, and in particular to a low-lead inorganic perovskite scintillator and a preparation method and application thereof. Background Art
[0002] High-energy X-rays have deep penetration capabilities and have become modern diagnostic tools in a variety of fields (e.g., industrial defect inspection, safety inspection, and medical imaging). Scintillators are a class of materials that can convert high-energy photons such as X-rays into low-energy ultraviolet and visible photons that are easily detected by traditional photodetectors. Therefore, indirect detectors based on scintillators have broader application prospects than complex direct X-ray detectors (X-rays converted into electrons). Cs-Pb-Br perovskite scintillators have the advantages of high light yield, fast decay, and solution processing, and are considered to be a favorable alternative to commercially available CsI:Tl scintillators. However, the radiation stability of Cs-Pb-Br perovskite scintillators is not ideal, and the content of toxic element lead is high, which makes it difficult to fully meet the needs of practical applications, which seriously hinders its large-scale application.
[0003] Therefore, it is of great significance to develop a Cs-Pb-Br perovskite scintillator with excellent optical properties, low lead content, and can be used for efficient X-ray imaging. Summary of the invention
[0004] The object of the present invention is to provide a low-lead inorganic perovskite scintillator and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A low-lead inorganic perovskite scintillator (chemical formula Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 ), which consists of Cs 4 (Pb 1-x Zn x )Br 6 Nanoparticles and embedded Cs 4 (Pb 1-x Zn x )Br 6 Nanoparticles of Cs(Pb 1-x Zn x )Br 3 Nanoparticles, 0.6 <x<1。
[0007] Preferably, the average particle size of the low-lead inorganic perovskite scintillator is less than 400 nm.
[0008] A method for preparing the low-lead inorganic perovskite scintillator as described above comprises the following steps:
[0009] 1) CsBr, PbBr 2 and 3-aminopropyltriethoxysilane dispersed in an organic solvent for solid-liquid heterogeneous interface reaction to prepare Cs 4 PbB 6 Nanoparticle dispersion, and ZnBr 2 Dissolve in ammonia water to make basic zinc bromide solution;
[0010] 2) Add basic zinc bromide solution to Cs 4 PbB 6 A water-assisted cation exchange reaction is carried out in a nanoparticle dispersion, and then the product is separated to obtain a low-lead inorganic perovskite scintillator.
[0011] Preferably, in step 1), the CsBr, PbBr 2 The molar ratio is 4 to 6:1.
[0012] Preferably, in step 1) the PbBr 2 , the dosage ratio of 3-aminopropyltriethoxysilane (KH550) is 1mmol:200μL~800μL.
[0013] Preferably, in step 1) the PbBr 2 , the dosage ratio of organic solvent is 1mmol:10mL~15mL.
[0014] Preferably, the organic solvent in step 1) is at least one of N,N-dimethylformamide and dimethyl sulfoxide.
[0015] Preferably, the solid-liquid heterogeneous interface reaction in step 1) is carried out at a temperature of 90° C. to 120° C., and the reaction time is 5 min to 10 min.
[0016] Preferably, the solid-liquid heterogeneous interface reaction in step 1) is carried out under stirring.
[0017] Preferably, in step 1) the PbBr 2 、ZnBr 2 The molar ratio is 1:1~2.
[0018] Preferably, the water-assisted cation exchange reaction in step 2) is carried out at a temperature of 90° C. to 120° C., and the reaction time is 5 min to 10 min.
[0019] Preferably, the water-assisted cation exchange reaction in step 2) is carried out under stirring.
[0020] Preferably, the product separation in step 2) comprises the following operations: adding the reaction solution to a centrifuge, adjusting the speed of the centrifuge to 6000 rpm to 8000 rpm, centrifuging for 3 min to 5 min, washing the solid obtained by centrifugation with ethanol, and then placing it in an oven at 50°C to 70°C for 20 h to 30 h.
[0021] A scintillator film comprises the above-mentioned low-lead inorganic perovskite scintillator.
[0022] An application of the low-lead inorganic perovskite scintillator as described above for X-ray imaging or radiation detection.
[0023] Principle of the invention: The invention adds a cation exchange promoter 3-aminopropyltriethoxysilane to the solid-liquid interface reaction system, and then adds a basic zinc bromide (chemical formula: Zn(OH)Br) solution to trigger a water-assisted cation exchange reaction to form Cs 4 PbB 6 / CsPbBr 3 phase, and induce Zn 2+ Entering the perovskite lattice to replace toxic Pb 2+ , achieving a large amount of Zn 2+ Doping finally yields a low-lead inorganic perovskite scintillator.
[0024] The beneficial effects of the present invention are as follows: the low-lead inorganic perovskite scintillator of the present invention has the advantages of excellent optical properties, high light yield, low lead content, etc., and can be used in the fields of X-ray imaging, radiation detection, etc., and its preparation method has the advantages of short cycle, mild conditions, strong repeatability, etc., and is easy to carry out large-scale industrial production and application.
[0025] Specifically:
[0026] 1) Compared with the traditional Cs-Pb-Br perovskite scintillator, the low-lead inorganic perovskite scintillator of the present invention has a lead content reduced by more than 40%, while maintaining excellent optical properties, and its fluorescence quantum efficiency can reach 96%. In addition, the average particle size of the scintillator (powder) is reduced to less than 400nm;
[0027] 2) The low-lead inorganic perovskite scintillator of the present invention has a 0D / 3D heterostructure and has a light yield of up to 18500photons / MeV under X-ray irradiation, which is high in light yield;
[0028] 3) The low-lead inorganic perovskite scintillator of the present invention can be used in fields such as X-ray imaging, radiation detection (for example, non-destructive detection, nuclear physics detection, etc.), and has a very broad application prospect;
[0029] 4) The low-lead inorganic perovskite scintillator of the present invention has a short preparation cycle, mild preparation conditions, high product stability, strong repeatability of the preparation method, and is easy to carry out large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 1 and 2 are XRD diagrams of the low-lead inorganic perovskite scintillator in Example 1 and the inorganic perovskite scintillators in Comparative Examples 1 to 4.
[0031] Figure 2 This is the XRD pattern of the inorganic perovskite scintillator in Comparative Example 5.
[0032] Figure 3 These are the SEM images and EDS energy spectra of the low-lead inorganic perovskite scintillator in Example 1.
[0033] Figure 4 The SEM image, particle size distribution image and EDS energy spectrum scanning image of the low-lead inorganic perovskite scintillator in Example 1 are shown.
[0034] Figure 5 XRD diagram, emission spectrum diagram, fluorescence lifetime diagram at 390nm 0D STE emission, and fluorescence lifetime diagram at 520nm 3D exciton emission of the low-lead inorganic perovskite scintillator in Example 1 and the inorganic perovskite scintillator in Comparative Example 6.
[0035] Figure 6 This is a graph showing the fluorescence quantum efficiency test results of the low-lead inorganic perovskite scintillator in Example 1.
[0036] Figure 7 It is a radiation luminescence spectrum diagram of the scintillator film excited by X-rays in Example 1, as well as a real picture and an image diagram of X-ray imaging of a ballpoint pen. DETAILED DESCRIPTION
[0037] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0038] Embodiment 1:
[0039] A low-lead inorganic perovskite scintillator, the preparation method of which is as follows:
[0040] 1) 4 mmol of CsBr and 1 mmol of PbBr 2 500 μL of 3-aminopropyltriethoxysilane was added to 10 mL of N,N-dimethylformamide and stirred at 90 °C for 5 min to prepare Cs 4 PbB 6 Nanoparticle dispersion (white turbid solution), and 1 mmol of ZnBr 2Dissolve it in 2 mL of water, and then add 20 μL of ammonia water with a mass fraction of 36% to prepare a zinc bromide hydroxide solution;
[0041] 2) Add the zinc bromide hydroxide solution to the Cs 4 PbBr 6 nanoparticle dispersion. Stir at 90 °C for 5 min, then add the reaction solution (green turbid solution) to a centrifuge. Adjust the centrifuge speed to 6000 rpm and centrifuge for 3 min. Then take the centrifuged solid, wash it with 10 mL of ethanol and centrifuge again. Then take the centrifuged solid and place it in an oven at 60 °C for 24 h to obtain a low-lead inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 0.4 Zn 0.6 )Br 6 / Cs(Pb 0.4 Zn 0.6 )Br 3 , denoted as Zn-1.0).
[0042] A scintillator film, the preparation method thereof is as follows:
[0043] a) Disperse 0.4 g of the above-mentioned low-lead inorganic perovskite scintillator into 0.5 mL of ethyl acetate, then add 4 mL of commercial polydimethylsiloxane (PDMS), stir vigorously for 0.5 h, and then perform vacuum degassing treatment to obtain a scintillator colloidal solution;
[0044] b) Pour the scintillator colloidal solution into a square mold with a side length of 5 cm, and then place it in an oven at 100 °C for annealing for 1 h to obtain a scintillator film.
[0045] Example 2:
[0046] A low-lead inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 , 0.6 < x < 0.8, denoted as Zn-1.25), except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "1.25 mmol", and the rest is exactly the same as Example 1.
[0047] Example 3:
[0048] A low-lead inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br6 / Cs(Pb 1-x Zn x )Br 3 , 0.6 < x < 0.8, denoted as Zn-1.5), except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "1.5 mmol", and the rest is exactly the same as in Example 1.
[0049] Example 4:
[0050] A low-lead inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 , 0.6 < x < 0.8, denoted as Zn-1.75), except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "1.75 mmol", and the rest is exactly the same as in Example 1.
[0051] Example 5:
[0052] A low-lead inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 , 0.6 < x < 0.8, denoted as Zn-2.0), except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "2.0 mmol", and the rest is exactly the same as in Example 1.
[0053] Comparative Example 1:
[0054] An inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 , 0 < x < 0.6, denoted as Zn-0.75), except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "0.75 mmol", and the rest is exactly the same as in Example 1.
[0055] Comparative Example 2:
[0056] An inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 , 0 < x < 0.5, denoted as Zn-0.5). Except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "0.5 mmol", the rest is exactly the same as in Example 1.
[0057] Comparative Example 3:
[0058] An inorganic perovskite scintillator (chemical formula: Cs 4 (Pb 1-x Zn x )Br 6 / Cs(Pb 1-x Zn x )Br 3 , 0 < x < 0.25, denoted as Zn-0.25). Except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "0.25 mmol", the rest is exactly the same as in Example 1.
[0059] Comparative Example 4:
[0060] An inorganic perovskite scintillator (chemical formula: Cs 4 PbBr 6 / CsPbBr 3 , denoted as Zn-0.0). Except that when preparing, the dosage of ZnBr 2 in step 1) is adjusted from "1 mmol" to "0", the rest is exactly the same as in Example 1.
[0061] Comparative Example 5:
[0062] An inorganic perovskite scintillator. Except that when preparing, "ZnBr 2 " in step 1) is replaced with an equimolar amount of "NH 4 Br", the rest is exactly the same as in Example 1.
[0063] Comparative Example 6:
[0064] An inorganic perovskite scintillator, and its preparation method is as follows:
[0065] Mix 4 mmol of CsBr and 1 mmol of PbBr 2Add 10 mL of N,N-dimethylformamide, stir at 90 ° C for 5 minutes, then add the reaction solution (yellow-green turbid solution) into the centrifuge, adjust the speed of the centrifuge to 8000 rpm, centrifuge for 5 minutes, then take the solid obtained by centrifugation, wash it with 10 mL of ethanol and centrifuge it again, then take the solid obtained by centrifugation and place it in an oven at 60 ° C for 24 hours to obtain an inorganic perovskite scintillator.
[0066] Performance Test:
[0067] 1) The X-ray diffraction (XRD) patterns of the low-lead inorganic perovskite scintillator in Example 1 and the inorganic perovskite scintillators in Comparative Examples 1 to 4 are as follows: Figure 1 (The small picture on the left in the figure is the actual picture of the sample and the luminescence picture under 365nm ultraviolet light).
[0068] Depend on Figure 1 It can be seen that: with the increase of ZnBr 2 As the dosage increases, the phase of the prepared product gradually changes to Cs 4 PbB 6 / CsPbBr 3 , and the luminescence intensity is getting higher and higher, and some characteristic peaks are consistent with the standard card Cs 4 PbB 6 (PDF#73-2478), some characteristic peaks are consistent with the standard card CsPbBr 3 (PDF#75-0412) is consistent, indicating that Cs 4 PbB 6 / CsPbBr 3 Perovskite materials.
[0069] 2) The XRD pattern of the inorganic perovskite scintillator in Comparative Example 5 is as follows Figure 2 (The small picture in the upper right corner of the figure is the actual picture of the sample and the luminescence picture under 365nm ultraviolet light).
[0070] Depend on Figure 2 It can be seen that: using ammonium bromide (NH 4 The product prepared by the method of using Br) only has the physical phase of the raw material CsBr, and no luminescence phenomenon is observed under 365nm ultraviolet light, indicating that there is no Cs 4 PbB 6 / CsPbBr 3 Phase formation.
[0071] It can be seen that the present invention uses a cation exchange promoter KH550 in a solid-liquid reaction system and simultaneously adds a large amount of Zn 2+ The basic zinc bromide solution can trigger the Cs 4 PbB 6 / CsPbBr 3 phase formation and achieve a large amount of Zn 2+ Doping into the perovskite lattice to replace toxic Pb 2+ .
[0072] 3) The scanning electron microscope (SEM) image and energy dispersive X-ray spectrum (EDS) image of the low-lead inorganic perovskite scintillator in Example 1 are as follows: Figure 3 (a is a SEM image, b is an EDS spectrum image), and the element analysis results corresponding to the EDS spectrum image are shown in the following table:
[0073] Table 1 Element analysis results corresponding to EDS spectrum
[0074] Element Type Weight percentage (%) Atomic percentage (%) Si 23.11 49.22 Zn 6.98 6.21 Br 44.03 32.96 Cs 16.82 7.57 Pb 9.06 4.04 sum 100 100
[0075] Depend on Figure 3 As shown in Table 1, the atomic percentages of Pb and Zn are 4.04% and 6.21% respectively, indicating that the low-lead inorganic perovskite scintillator in Example 1 is similar to Cs 4 PbB 6 / CsPbBr 3 The lead content is reduced by more than 40% compared to scintillators.
[0076] 4) The SEM image, particle size distribution image and EDS energy spectrum scanning image of the low-lead inorganic perovskite scintillator in Example 1 are as follows Figure 4 (a is a SEM image, b is a particle size distribution image, and c is an EDS energy spectrum scanning image).
[0077] Depend on Figure 4 From a and b in FIG, it can be seen that the average particle size of the low-lead inorganic perovskite scintillator is less than 400 nm, which is conducive to the preparation of a scintillator film with good transparency.
[0078] Depend on Figure 4 From the c in the figure, we can see that the Zn element is evenly distributed on the scintillator particles, indicating that a large amount of Zn 2+ The ions are uniformly doped into the perovskite lattice.
[0079] 5) The XRD pattern, emission spectrum (254nm and 365nm excitation) pattern, fluorescence lifetime pattern at 390nm 0D STE emission, and fluorescence lifetime pattern at 520nm 3D exciton emission of the low-lead inorganic perovskite scintillator in Example 1 and the inorganic perovskite scintillator in Comparative Example 6 are as follows: Figure 5 (a is the XRD diagram, b is the emission spectrum diagram, c is the fluorescence lifetime diagram at 390nm 0D STE emission, and d is the fluorescence lifetime diagram at 520nm 3D exciton emission).
[0080] Depend on Figure 5It can be seen from a in that the characteristic diffraction peak of the low-lead inorganic perovskite scintillator in Example 1 moves to a higher diffraction angle compared with the inorganic perovskite scintillator in Comparative Example 6, indicating that the Zn with a smaller ion radius 2+ After heavy doping, the lattice shrinks, further proving that a low-lead inorganic perovskite scintillator has been obtained.
[0081] Depend on Figure 5 It can be seen from b that the broadband emission of the low-lead inorganic perovskite scintillator in Example 1 is within the 254nm excitation range and near 390nm is attributed to 0D Cs 4 PbB 6 The narrow-band emission around 520 nm is attributed to the self-trapped exciton (STE) emission of 3D CsPbBr 3 exciton emission; compared with the inorganic perovskite scintillator in Comparative Example 6, the PL intensity ratio of the low-lead inorganic perovskite scintillator in Example 1 under 0D STE emission is reduced, while the PL intensity ratio under 3D exciton emission is increased, indicating that large amounts of zinc doping are beneficial to energy transfer from 0D to 3D.
[0082] Depend on Figure 5 From c and d in Figure 1, it can be seen that under 254nm excitation, the broad emission of the low-lead inorganic perovskite scintillator in Example 1 and the inorganic perovskite scintillator in Comparative Example 6 at 390nm exhibits slow decay, with lifetimes of 117.97μs and 97.22μs, respectively. Their microsecond fluorescence lifetimes are consistent with the STE emission characteristics. In addition, under 365nm excitation, the lifetime of the low-lead inorganic perovskite scintillator in Example 1 at 520nm emission is greatly shortened (from 81.41ns to 30.2ns), showing accelerated exciton radiative recombination characteristics, which is attributed to the Zn 2+ The large amount of doping effectively promotes the transition from 0D Cs 4 PbB 6 to 3D CsPbBr 3 energy transfer, thereby accelerating the exciton radiative recombination and luminescence.
[0083] 6) The fluorescence quantum efficiency test results of the low-lead inorganic perovskite scintillator in Example 1 are shown in FIG. Figure 6 shown.
[0084] Depend on Figure 6 It can be seen that the fluorescence quantum efficiency of the low-lead inorganic perovskite scintillator in Example 1 is as high as 96%.
[0085] After testing (testing method is the same as above), the fluorescence quantum efficiency of the low-lead inorganic perovskite scintillators in Examples 2 to 5 is higher than 90%.
[0086] 7) The radiation luminescence spectrum of the scintillator film in Example 1 under X-ray excitation (excitation voltage of 50 keV, current of 70 μA) and the physical and imaging images of the ballpoint pen under X-ray imaging are shown in FIG. Figure 7 (a is the X-ray excited radiation luminescence spectrum, b is the actual picture and imaging picture of the ballpoint pen; the small picture on the left in a is the actual picture of the scintillator film in the luminous state).
[0087] Depend on Figure 7 From a in Example 1, we can see that the low-lead inorganic perovskite scintillator in Example 1 has a light yield of up to 18500 photons / MeV, which is higher than that of commercial Bi 4 Ge 3 O 12 (BGO crystal) and the inorganic perovskite scintillator in Comparative Example 6.
[0088] Depend on Figure 7 From b in FIG. 1 , it can be seen that: taking a ballpoint pen as the imaging object and performing X-ray imaging on it using the scintillator film in Example 1, the internal structural features of the ballpoint pen can be clearly seen.
[0089] After testing (the testing method is the same as above), the fluorescence quantum efficiency of the inorganic perovskite scintillator in Comparative Example 1 is 54%, and the light yield is 8400photons / MeV, which are significantly lower than the low-lead inorganic perovskite scintillator in the embodiment. In addition, the fluorescence quantum efficiency and light yield of the inorganic perovskite scintillators in Comparative Examples 2 and 3 are both lower.
[0090] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A low-lead inorganic perovskite scintillator, characterized in that: Composition includes Cs4(Pb 1-x Zn x )Br6 nanoparticles and embedded Cs4(Pb 1-x Zn x )Br6 nanoparticles of Cs(Pb 1-x Zn x )Br3 nanoparticles, 0.6 <x<1。 2. The low-lead inorganic perovskite scintillator according to claim 1, characterized in that: The average particle size of the low-lead inorganic perovskite scintillator is less than 400 nm.
3. A method for preparing a low-lead inorganic perovskite scintillator as claimed in claim 1 or 2, characterized in that: The following steps are involved: 1) dispersing CsBr, PbBr2 and 3-aminopropyltriethoxysilane in an organic solvent to carry out solid-liquid heterogeneous interface reaction to prepare a Cs4PbBr6 nanoparticle dispersion, and dissolving ZnBr2 in ammonia water to prepare a basic zinc bromide solution; 2) Adding basic zinc bromide solution to the Cs4PbBr6 nanoparticle dispersion to carry out water-assisted cation exchange reaction, and then separating the product to obtain a low-lead inorganic perovskite scintillator.
4. The preparation method according to claim 3, characterized in that: The molar ratio of CsBr and PbBr2 in step 1) is 4 to 6:1; the dosage ratio of PbBr2 and 3-aminopropyltriethoxysilane in step 1) is 1 mmol: 200 μL to 800 μL.
5. The preparation method according to claim 3 or 4, characterized in that: In step 1), the organic solvent is at least one of N,N-dimethylformamide and dimethyl sulfoxide.
6. The preparation method according to claim 3 or 4, characterized in that: Step 1) The solid-liquid heterogeneous interface reaction is carried out at a temperature of 90° C. to 120° C., and the reaction time is 5 min to 10 min.
7. The preparation method according to claim 3 or 4, characterized in that: Step 1) The molar ratio of PbBr2 to ZnBr2 is 1:1-2.
8. The preparation method according to claim 3 or 4, characterized in that: Step 2) The water-assisted cation exchange reaction is carried out at a temperature of 90° C. to 120° C., and the reaction time is 5 min to 10 min.
9. A scintillator film, characterized in that: Contains the low-lead inorganic perovskite scintillator according to claim 1 or 2.
10. Use of the low-lead inorganic perovskite scintillator according to claim 1 or 2 for X-ray imaging or radiation detection.